2014
DOI: 10.54172/mjsc.v29i1.268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on hematological parameters in male smokers in Al-Bayda city, Libya

Abstract: Tobacco smoking use is widely spread throughout the world. Tobacco smoking has been claimed to cause a wide variety of health problems such as atherosclerosis, mutagenesis of exposed cells and cancer. The effects of smoking on human health are serious and in many cases, deadly. The present study was done to investigate the effect of cigarette smoking on some hematological parameters in male smokers. The study is carried out on thirty Libyan male smokers, who smoked at least 10 cigarettes per day for at least15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…The study showed that total count of RBC, hemoglobin concentration and hematocrit levels were increased significantly among smokers in comparison to non-smokers. These findings are compatible with several other investigators [11][12][13][14][15][16][17] . These effects are possibly secondary to hypoxic stimuli exerted by smoking 16,17 .…”
Section: Discussionsupporting
confidence: 94%
“…The study showed that total count of RBC, hemoglobin concentration and hematocrit levels were increased significantly among smokers in comparison to non-smokers. These findings are compatible with several other investigators [11][12][13][14][15][16][17] . These effects are possibly secondary to hypoxic stimuli exerted by smoking 16,17 .…”
Section: Discussionsupporting
confidence: 94%